Experimental study of various central nervous system effects of eugenol in mice and rats - Sharma, M; Rauniar, GP; Das, BP (Health Renaissance, 2012)
Background: Eugenol is an essential component of many medicinal herbs. It is a member of the allylbenzene class of chemical compounds. Since years, it is being used in dental practice to relieve pain arising from pulpitis and dentinal hypersensitivity. There are few reports of anticonvulsant effect but further effects are less reported. Lack of comprehensive studies and data of eugenol on the central nervous system effects in animal models thus necessitates further research activities. Objective: To observe and evaluate various neuropharmacological effects like antinociceptive effect, anticonvulsant effect, effect on motor co-ordination, pentobarbital induced sleeping time and anxiolytic effect of eugenol in mice and rats. Methods: It was a quantitative experimental study done in the laboratory setting of the department of Clinical Pharmacology and Therapeutics. For each test, respective animal models were used. Animals were divided into three groups of six each, group I as control, group II as standard control and group III as test group. Results: Significant effects were observed in analgesic, anticonvulsant and sedative model whereas no significant effect as compared to control was observed in test of motor co-ordination and in behavioral models. Conclusion: This study shows eugenol to possess analgesic, anticonvulsant and sedative effect whereas it didn.t have any effect on models of anxiety. Various target sites have been implicated but this study doesn.t conclude a plausible mechanism behind all these observed effects. DOI: http://dx.doi.org/10.3126/hren.v10i3.7137 Health Renaissance; September-December 2012; Vol 10 (No.3);208-214